Effects of increasing dietary wheat middlings and dried distillers grains with solubles on nursery pig growth performance - De Jong, J.A.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 180 pigs (PIC 327 × 1050, initially 26.9 lb BW) were used in a 21-d trial to evaluate the effects of increasing dietary wheat middlings (midds) and dried distillers grains with solubles (DDGS) on nursery pig growth performance. Pens of pigs were balanced by initial BW and were randomly allotted to 1 of 6 dietary treatments with 5 replications per treatment. The 6 corn-soybean meal–based diets were arranged in a 2 × 3 factorial with main effects of DDGS (0 or 20%) and wheat midds (0, 10, or 20%). Diets were not balanced for energy, so as wheat midds increased, dietary energy concentration decreased. Overall (d 0 to 21), no DDGS × wheat midds interactions (P > 0.12) were observed. Pigs fed increasing wheat midds had decreased (linear, P < 0.02) ADG and poorer (linear, P < 0.01) F/G. Feed cost/pig and revenue/pig both decreased (linear, P < 0.02) with increasing wheat midds. Feeding pigs a diet containing 20% DDGS did not affect growth performance (P > 0.59) but decreased (P < 0.005) feed cost/pig. These data suggest that adding DDGS to diets containing wheat midds can be used to decrease feed costs when formulating nursery pig diets; however, increasing wheat midds decreased growth rate and economic return in this experiment.
Keywords: Swine; DDGS; Nursery pig; Wheat middlings